The Cultural Value of the Kayori Ceremony of the Pendau Tribe as Seen from the Civic Culture of the Siweli Village Community, Balaesang District - Cinta Arfa; Shofia Nurun Alunur; Hasdin; Nasran; Sunarto Amus; Sukmawati (ASANKA : Journal of Social Science and Education, 2026)
Previous studies on the Kayori Ceremony of the Pendau Tribe have tended to focus on linguistic and literary analysis, leaving a research gap in the perspective of Civic Education. This study aims to fill this gap by exploring the cultural values within the Kayori Ceremony and its unique contribution to the formation of civic culture in Siweli Village. Using a descriptive qualitative method with an ethnographic approach, data were collected through participant observation, in-depth interviews with 8 informants (traditional leaders, village officials, and youth), and documentation. The novelty of this research reveals that the Kayori Ceremony is not merely a mystical ritual but also functions as a "social laboratory" that internalizes the values of cooperation, religiosity, and social harmony as the foundation of local civic culture. Preservation challenges include internal factors, such as traditional leaders' commitment, as well as external factors, such as modernization. Efforts to preserve it through value transmission to the younger generation represent a form of civic responsibility. This study concludes that the internalization of Kayori strengthens civic identity and social integration within the framework of local wisdom, aligning with the pillars of Pancasila democracy.